The role of 3-tesla diffusion-weighted magnetic resonance imaging in selecting prostate cancer patients for active surveillance - Jeong, Chang Wook (Prostate Int, 2014)
PURPOSE: Differentiating significant cancer from insignificant cancer is a major challenge in active surveillance (AS) for prostate cancer. We evaluated whether the apparent diffusion coefficient (ADC) grade from 3-T diffusion-weighted magnetic resonance imaging (DW-MRI) is useful to exclude men with unfavorable pathological features from men meeting current AS eligibility criteria. METHODS: Among patients who underwent radical prostatectomy, 117 potential AS candidates defined according to 2013 European Association of Urology guidelines who had undergone preoperative 3-T DW-MRI were included. A blinded uro-radiologist graded the level of suspicion from the ADC map using the Likert scale from 1 to 5. The rate of unfavorable pathological features was evaluated according to ADC grade. Unfavorable pathological features were defined as non–organ-confined disease or pathological Gleason score≥7 (4+3). The associations between unfavorable pathological features and clinical variables including ADC grade (>3 vs. ≤3) were evaluated using logistic regression analysis. RESULTS: The rates of unfavorable pathological features were 0.0% (0/14), 2.9% (1/34), 5.4% (2/37), 25.0% (6/24), and 37.5% (3/8) from grades 1 to 5 (P=0.002). The predictive accuracy was as high as 0.804. The rates were significantly different between low (≤3, 3.5%) and high (>3, 28.1%, P<0.001) grades. The sensitivity, specificity, and positive and negative predictive values were 75.0%, 78.1%, 28.1%, and 96.5%. ADC grade (odds ratio [OR], 10.696; 95% confidence interval [CI], 2.675–42.773) was significantly associated with unfavorable pathological features, even after adjusting for other variables (OR, 11.274; 95% CI, 2.622–48.471). CONCLUSIONS: ADC grade from 3-T DW-MRI is useful to predict men with unfavorable pathologic features from AS candidates.